2018
DOI: 10.1007/s00784-018-2526-7
|View full text |Cite
|
Sign up to set email alerts
|

Does the skin color of patients influence the treatment decision-making of dentists? A randomized questionnaire-based study

Abstract: Skin color played an important role in dentists' treatment decisions. Professionals may contribute unconsciously to the propagation and replication of racial discrimination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
51
1
9

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 50 publications
(65 citation statements)
references
References 48 publications
4
51
1
9
Order By: Relevance
“…Beyond the influence of the media, satisfaction with appearance is intimately related to the social interaction that this subjective condition provides, especially in young individuals who want to be accepted into a social group 25 . Our results corroborate the findings of previous studies, in which women and younger subjects show greater desire for esthetic treatment in plastic surgery 23 and dentistry 5,[20][21][22] . Similarly, our study demonstrated that individuals satisfied with their dental color and dental appearance reported less desire for dental esthetic treatment.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Beyond the influence of the media, satisfaction with appearance is intimately related to the social interaction that this subjective condition provides, especially in young individuals who want to be accepted into a social group 25 . Our results corroborate the findings of previous studies, in which women and younger subjects show greater desire for esthetic treatment in plastic surgery 23 and dentistry 5,[20][21][22] . Similarly, our study demonstrated that individuals satisfied with their dental color and dental appearance reported less desire for dental esthetic treatment.…”
Section: Discussionsupporting
confidence: 92%
“…Esthetics is a very important concept to the general population and has been considered a key component of social interaction. This media pressure for a better look has increased the demand for esthetic procedures, especially in women and young people 5,[20][21][22][23] . Women are more concerned about health and more dissatisfied with their appearance 5 and are more likely to turn to esthetic procedures 20,21 , such as plastic surgery 23 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…33 A recent study carried by our group in four different cities in Brazil, including Pelotas, observed that black patient had less risk of receiving replacement of ill-adapted amalgam restoration with composite resin and finishing and polishing when compared with the white patient even as black patients receive referrals for cheaper treatments. 34 In this way, it was investigated the influence of the skin color on the decision to extract or retain a decayed tooth. 35 The results showed significative influence of skin color on dentist's decision make treatment with worse results associated with black skin color.…”
Section: Discussionmentioning
confidence: 99%
“…Diversos estudos têm demonstrado que as condutas clínicas variam entre os cirurgiõesdentistas de diferentes países [7][8][9][10][11][12][13] , demonstrando um perfil altamente curativista e intervencionista dos profissionais, os quais tendem a intervir em lesões iniciais de cárie e em restaurações com manchamento marginal, sem que existade fatoa necessidade para tal [9][10][11] . Desta forma, o ensino da Odontologia minimamente invasiva apresenta um contexto muito interessante para problematização da Odontologia tecnicista.…”
Section: Introductionunclassified